Unravelling Determinant Factors That Drive The Effectiveness of Compensation Practice (Qualitative Study at Banaran 9 Resto Coffee and Tea) - Heryadarma, Mirzam; Adhi Pradana, Handrio; Nurdiana Dihan, Fereshti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This study aims to analyze the implementation of compensation practices at Banaran 9 Resto Coffee and Tea, a government-owned culinary company with eight branches spread across Central Java. The research employs a qualitative case study approach involving employees from various levels at Banaran 9 Resto Coffee and Tea as the primary informants amounted to eight participants. The provision of compensation at Banaran 9 Resto Coffee and Tea involves a combination of various types of practices, including direct compensation, indirect compensation, and non-financial compensation. Direct compensation, such as salary and bonuses, has been proven to enhance employee performance and motivation. Indirect compensation, such as insurance and cafeteria facilities, contributes to improved social well-being and employee loyalty. Meanwhile, non-financial compensation, such as flexible selection of days off, promotion opportunities, and training, positively impacts productivity and employee career development. The research findings indicate that the implementation of a combination of various types of compensation practices at Banaran 9 Resto Coffee and Tea has been effective. The majority of employees express satisfaction with the compensation they receive, which contributes to increased performance and a high level of employee retention. This study provides profound insights into the diverse implementation of compensation at Banaran 9 Resto Coffee and Tea while reinforcing the important role of compensation as a reciprocal acknowledgment of employee contributions.